Acceptance and willingness to pay for health-enhancing bakery products – Empirical evidence for young urban Russian consumers. (December 2015) - Bruschi, Viola; Teuber, Ramona; Dolgopolova, Irina
Highlights: We assess the acceptance and WTP for two health-enhancing bakery products. Participants are young Russians either in Moscow or Irkutsk. Health-enhancing connotation of the products influences participants' WTP positively. Functional bread rolls appear more suitable to be connected with health-enhancing food. Abstract: Our study provides first empirical evidence on young Russian consumers' attitudes towards novel functional bakery products. We employ two different bakery products, namely bread rolls and biscuits, in our experimental auctions. Both products are derived from purple wheat, an old wheat variety that is naturally rich in anthocyanins (ACNs). ACNs are assumed to possess anti-inflammatory, anti-cancer, anti-diabetic and ocular-health-enhancing properties. Participants are 207 students aged 18–30 years from Moscow and Irkutsk. Our results indicate a low level of knowledge about ACNs among participants. However, our results also show that in the presence of information about the health-enhancing characteristics most participants value these products over base products. Our findings also reinforce the idea that the base product matters. Purple wheat bread rolls were better accepted than purple wheat biscuits. Moreover, our results also highlight that the information strategy matters. Participants in our study exhibited a higher willingness to pay for purple wheat biscuits under an old variety information scenario in comparison to an anthocyanin information scenario. Moreover, while our results indicate no significant difference in the perception of the anthocyanin attribute between the two cities, the perception of old grain variety products was slightly different. The share of respondents considering old variety products as healthy was significantly higher in Irkutsk, whereas the share of respondents considering these products as exclusive was significantly higher in Moscow. Thus, while planning future marketing strategies such differences in underlying motives should be taken into account.